Mechanism and Potential Target of Blood-Activating Chinese Botanical Drugs Combined With Anti-Platelet Drugs: Prevention and Treatment of Atherosclerotic Cardiovascular Diseases - Li, Dan; Li, Yujuan; Yang, Shengjie; Yu, Zongliang; Xing, Yanwei; Wu, Min (Frontiers in Pharmacology, 2022)
Abstract Atherosclerosis is the leading cause of coronary heart disease, cerebral infarction, and peripheral vascular diseases. In addition, various thrombotic events secondary to cardiovascular and cerebrovascular diseases have significantly increased worldwide mortality rates. It is necessary to find new antiplatelet drugs and reduce the resistance to antiplatelet drugs to prevent and treat atherosclerosis. Blood-activating Chinese herbs (BAC herbs) have been shown to improve haemodynamics and haemorheology, and to inhibit thrombosis, atherosclerosis, myocardial ischaemia, and inflammation. Modern medical research has identified that the combination of BAC herbs and antiplatelet drugs, such as aspirin or clopidogrel, not only enhances antiplatelet effects, but also reduces the risk of bleeding and protects the vascular endothelium. In this review, we will focus on the related targets and signalling pathways of anti-atherosclerotic treatments involving a combination of BAC herbs and antiplatelet drugs reported in recent years.